SLC45A4 promotes glycolysis and prevents AMPK/ULK1‐induced autophagy in TP53 mutant pancreatic ductal adenocarcinoma. (2nd June 2021) - Chen, Wenying; Huang, Fengting; Huang, Jing; Li, Yuanhua; Peng, Juanfei; Zhuang, Yanyan; Huang, Xianxian; Lu, Liting; Zhu, Zhe; Zhang, Shineng
Abstract: Background: Somatic mutations of the TP53 gene occur frequently in pancreatic ductal adenocarcinoma (PDA). Solute carrier family 45 member A4 (SLC45A4) is a H + ‐dependent sugar cotransporter. The role of SLC45A4 in PDA, especially in TP53 mutant PDA, remains poorly understood. Methods: We explored the TCGA datasets to identify oncogenes in TP53 mutant PDA. MTS [3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium], colony formation and 5‐ethynyl‐2′‐deoxyuridine (Edu) assays were performed to investigate the function of SLC45A4 in vitro . Glucose consumption, lactate production and ATP production were detected to evaluate glucose utilization. Extracellular acidification rate and oxygen consumption rate assays were used to evaluate glycolysis and oxidative phosphorylation. The subcutaneous xenotransplantation models were conducted to explore the function of SLC45A4 in vivo . RNA‐sequencing and gene set enrichment analysis were employed to explore the biological alteration caused by SLC45A4 knockdown. Western blotting was performed to evaluate the activation of glycolysis, as well as the AMPK pathway and autophagy. Results: SLC45A4 was overexpressed in PDA for which the expression was significantly higher in TP53 mutant PDA than that in wild‐type PDA tissues. Moreover, high level of SLC45A4 expression was tightly associated with poor clinical outcomes in PDA patients. Silencing SLC45A4 inhibited proliferation in TP53 mutant PDA cells. Knockdown of SLC45A4 reduced glucose uptake and ATP production, which led to activation of autophagy via AMPK/ULK1 pathway. Deleting SLC45A4 in TP53 mutant HPAF‐II cells inhibited the growth of xenografts in nude mice. Conclusions: The present study found that SLC45A4 prevents autophagy via AMPK/ULK1 axis in TP53 mutant PDA, which may be a promising biomarker and therapeutic target in TP53 mutant PDA. Abstract : Knockdown of solute carrier family 45 member 4 (SLC45A4) reduced glucose uptake and ATP production, which led to activation of autophagy via the AMPK/ULK1 pathway in TP53 mutant pancreatic ductal adenocarcinoma cells.